LITERASI DIGITAL DAN DIGITALISASI KESENIAN DI DESA MEKARMUKTI - Elsen, Rickard; Ramadhan, Iwan; Hamzah, Muhamad; Kaulan, Muhammad Denanda; Nurapipah, Nida; Septiyani, Tiara; Amelia, Melina; Indallah, Aghniya Qolbin; Putri, Salsabilah Triana; Romansah, Ubad; Munawar, Deni Wildan; Mubarok, Zam Zam; Abadi, Manza Restu; Hanif, Muhammad; Jaelani, Iqbal Waliyuddin Sidiq; Assholih, Mukhtar; Apriliansah, Rudi; Nurzaman, Ikbal Saputra; Septiana, Yuga; Saputra, Raihan Rafif Syaefudin; Alamsyah, Reza Bachtiar; Rosandi, Ujang Ahmad (Institut Teknologi Garut, 2025)
This study explores the role of students in the Mekarmukti village community over a period of one month, specifically through real work lecture activities with digital literacy work programs, education, physical development, and collaboration with the village government and other campuses. These activities involve introducing social media to artists, teaching Bebras and Information and Communication Technology Volunteers, teaching in early childhood education (PAUD), and optimizing Micro, Small, and Medium Enterprises through the introduction of Google Maps, rebranding, and employee needs analysis. In addition, students participated in helping prepare for the 79th Anniversary of the Republic of Indonesia, teaching the Koran, cleaning the mosque environment, painting Posyandu and PAUD, and helping with the physical construction of the sports building. This study uses a qualitative method with a case study approach to analyze the impact and contribution of students in these activities.